Autentusitas dan Gradualitas Al-qur'an - Amri Amri (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Muslim ummah claim that only the Qur’an is really authentic and gradual  for its revelation. This claim is based on various verses of the Qur’an itself. The  claim, although is considered saintific by all Muslims it is not accepted by non- Muslims. To make it more accepted scientificly by all believers (Muslims and  non-Muslims), it needs to prove its authenticity and graduality of revelation  through historical approach. In order to prove the originality of the Qur'an, the  Muslims should not only use the evidence in the form of verse, but historical facts  can not be denied by another Ummah. Therefore, describes Autensitas and  Gradualitas Qur'an based on historical evidence is strengthened by the arguments  of the Qur'an needs to be.